2004
DOI: 10.1046/j.1351-5101.2003.00734.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical callosum syndrome in a case of multiple sclerosis

Abstract: This case report confirms that a clinical callosal disconnection could be observed in multiple sclerosis. Moreover, this case describes a new kind of strange manual behavior related to callosal disconnection. This behavior could neither be considered as a diagonistic dyspraxia nor as an alien hand, but they evoke rather a conflict of intentions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Tasks which evaluate transfer of auditive, motor and somesthesic information also shown a deficit in interhemispheric transfer [22][23][24]. Some rare cases of MS patients presenting a real syndrome of callosal disconnection were also reported [25]. Ipsilateral Silent Period (ISP) paradigm revealed that transcallosal conduction is significantly slower in MS patients [26].…”
Section: Introductionmentioning
confidence: 99%
“…Tasks which evaluate transfer of auditive, motor and somesthesic information also shown a deficit in interhemispheric transfer [22][23][24]. Some rare cases of MS patients presenting a real syndrome of callosal disconnection were also reported [25]. Ipsilateral Silent Period (ISP) paradigm revealed that transcallosal conduction is significantly slower in MS patients [26].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion tensor tractography (DTT), derived from diffusion tensor imaging (DTI), allows for threedimensional visualization of CC fibers [12][13][14][15]. Therefore, DTT has been used for the assessment of disruptions of CC fibers in patients with brain injury, including diffuse axonal injury (DAI) and stroke [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Here we report a single case study of a 47-year-old woman, with 35-year history of multiple sclerosis (MS) who presented with alien hand signs. Alien hand has been described in MS only occasionally, generally associated with callosal involvement [7, 8]. Even though inflammatory demyelination and axon damage in the corpus callosum are prominent features of MS, clinical manifestations of alien hand or other signs of callosal disconnection, such as callosal apraxia or unilateral agraphia, have been scarcely reported.…”
Section: Introductionmentioning
confidence: 99%